1992
DOI: 10.1002/1097-0142(19920315)69:6<1498::aid-cncr2820690631>3.0.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

Ascending myelitis after intensive chemotherapy and radiation therapy in children with cranial parameningeal sarcoma

Abstract: In 1977, a program of early, wide‐field radiation therapy (RT) to the central nervous system and repeated lumbar intrathecal (IT) medications along with systemic chemotherapy was begun by the Intergroup Rhabdomyosarcoma Study (IRS) for patients younger than 21 years of age with cranial parameningeal sarcoma and a high risk of meningeal extension. From 1977 until 1987, 149 eligible patients with high‐risk cranial parameningeal sarcoma were enrolled in IRS trials. None had evidence of lower extremity or sphincte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0
1

Year Published

1993
1993
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 26 publications
0
13
0
1
Order By: Relevance
“…Clinical studies using CEDD of paclitaxel showed a similar complication, which was attributed to leakage of paclitaxel into the subarachnoid space (29). Accidental intrathecal administration of other anti-microtubule agents has been shown to produce a wide range of complications and should be avoided (31,32).…”
Section: Discussionmentioning
confidence: 99%
“…Clinical studies using CEDD of paclitaxel showed a similar complication, which was attributed to leakage of paclitaxel into the subarachnoid space (29). Accidental intrathecal administration of other anti-microtubule agents has been shown to produce a wide range of complications and should be avoided (31,32).…”
Section: Discussionmentioning
confidence: 99%
“…More ominous is the transverse myelopathy seen after intensive intrathecal chemotherapy for parameningeal rhabdomyosarcoma, which has resulted in devastating complications and death [9]. Raney et al report, however, that no additional cases have been seen after reducing the doses and number of cycles of the three intrathecal drugs used (methotrexate, hydrocortisone, and cytarabine) [9].…”
Section: Discussionmentioning
confidence: 99%
“…Raney et al report, however, that no additional cases have been seen after reducing the doses and number of cycles of the three intrathecal drugs used (methotrexate, hydrocortisone, and cytarabine) [9].…”
Section: Discussionmentioning
confidence: 99%
“…4 The latency to onset of neurological symptoms is extremely variable, from within a few hours of the first intrathecal chemotherapy injection to several months after completion of a course of several injections. 54 Patients typically develop back or leg pain and a rapidly ascending flaccid paraparesis with a sensory level and bowel/bladder involvement. 53 The syndrome can occur with or without concomitant systemic chemotherapy or spinal irradiation.…”
Section: Myelopathymentioning
confidence: 99%